Cooperativity between sodium ions and water molecules facilitates lipid mobility in model cell membranes. Issue 15 (27th March 2023) - Chattopadhyay, Madhurima; Krok, Emilia; Orlikowska-Rzeznik, Hanna; Piatkowski, Lukasz
Abstract : Water hydrating lipid membranes plays a major role in facilitating lipid diffusion. However, once the membrane hydration layer is perturbed an intricate cooperation between water and specific ions is required to maintain membrane fluidity. Abstract : Cellular membranes are surrounded by an aqueous buffer solution containing various ions, which influence the hydration layer of the lipid head groups. At the same time, water molecules hydrating the lipids play a major role in facilitating the organisation and dynamics of membrane lipids. Employing fluorescence microscopy imaging and fluorescence recovery after photobleaching measurements, we demonstrate that the cooperativity between water and sodium (Na + ) ions is crucial to maintain lipid mobility upon the removal of the outer hydration layer of the lipid membrane. Under similar hydration conditions, lipid diffusion ceases in the absence of Na + ions. We find that Na + ions (and similarly K + ions) strengthen the water clathrate cage around the lipid phosphocholine headgroup and thus prevent its breaking upon removal of bulk water. Intriguingly, Ca 2+ and Mg 2+ do not show this effect. In this article, we provide a detailed molecular-level picture of ion specific dependence of lipid mobility and membrane hydration properties.